Characterization of AlInN layer grown on GaN/Sapphire substrate by MOCVD - Wei-Ching Huang; Edward-Yi Chang; Yuen-Yee Wong; Kung-Liang Lin; Yu-Lin Hsiao; Chang, Fu Dee; Burhanuddin Yeop Majlis (Universiti Kebangsaan Malaysia, 2013)
The AlInN layers have been grown with different growth parameters on GaN/sapphire substrates by metal-organic chemical vapor deposition (MOCVD). The effects of growth parameters such as pressure and temperature on the Al incorporation during AlInN material growth have been investigated. The results showed that lower pressure provides a tendency for higher Al incorporating in the AlInN layer. Besides, as the temperature was increased from 700°C to 780°C, an estimation of 4% reduction on the indium composition has been observed for each 20°C increment. XRD analysis showed that the best crystal quality of AlInN occured at 80% Al composition because of the higher lattice matching with GaN. Based on the above criteria, an Al0.8In0.2N/GaN HEMT device with 2 μm gate length has also been fabricated. The DC characteristics showed a saturated current, Idss of 280 mA/mm and transconductance of 140 mS/mm.